2018
DOI: 10.1016/j.eja.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical disaggregation of polygon maps of average crop yields by area-to-point kriging

Abstract: Crop yield data are often available as statistics of areas, such as administrative units, generated by national agricultural surveys and censuses. This paper shows that such areal data can be used in area-to-point kriging (ATP kriging) to estimate the crop yield at the nodes of a fine grid that discretizes the study area, so that a more detailed map of the crop yield is obtained. The theory behind ATP kriging is explained, and illustrated with a onedimensional simulation study and two real-world case studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For REML, the approach as described by Brus et al (2018) was applied. For MML, the posterior mode of φ was calculated using the Bayesian approach with a uniform prior for φ.…”
Section: Estimation and Prediction With Reml And MMLmentioning
confidence: 99%
See 4 more Smart Citations
“…For REML, the approach as described by Brus et al (2018) was applied. For MML, the posterior mode of φ was calculated using the Bayesian approach with a uniform prior for φ.…”
Section: Estimation and Prediction With Reml And MMLmentioning
confidence: 99%
“…6 for millet. Covariates for the trends as suggested by Brus et al (2018) are used: for millet no covariates, and for sorghum four covariates are shown and briefly explained in Online Resource F.…”
Section: Real Case Study: Crop Yield Datamentioning
confidence: 99%
See 3 more Smart Citations